2006
DOI: 10.1007/s10709-005-1427-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogenetic Analysis of Petunia Juss. (Solanaceae)

Abstract: Representatives from 11 Petunia Jussieu species in south and southeast Brazil were compared with two Calibrachoa La Llave & Lex., one Bouchetia Dunal, and two Nierembergia Ruiz & Pav. taxa in relation to DNA molecular variability. A total of 4532 base pairs related to one nuclear, five plastidial and one mitochondrial systems was investigated. Petunia and Calibrachoa, although separated among themselves, clearly differentiate from the two other genera. Despite the fact that the Petunia species do not show mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 39 publications
(35 reference statements)
5
59
0
Order By: Relevance
“…Although P. axillaris and P. integrifolia can be crossed in the laboratory, no hybrids were detected in sympatric populations (Ando et al, 2001). Recent DNA sequence analyses confirm that the species are closely related and that interspecific relationships are poorly resolved Kulcheski et al, 2006). Further work with more polymorphic markers may soon resolve ambiguities and provide a robust phylogeny of the genus.…”
Section: Introductionmentioning
confidence: 99%
“…Although P. axillaris and P. integrifolia can be crossed in the laboratory, no hybrids were detected in sympatric populations (Ando et al, 2001). Recent DNA sequence analyses confirm that the species are closely related and that interspecific relationships are poorly resolved Kulcheski et al, 2006). Further work with more polymorphic markers may soon resolve ambiguities and provide a robust phylogeny of the genus.…”
Section: Introductionmentioning
confidence: 99%
“…We have selected the solanaceous genus Petunia (2n ¼ 14) for our studies on the genetics of pollination syndromes. Petunia is native to South America and has been divided into up to 16 species, but the phylogeny of the genus has not yet been rigorously resolved (Ando et al 2005;Kulcheski et al 2006;Lorenz-Lemke et al 2006, Stehmann et al 2009). Most members of the genus present characteristics of beepollinated species (typical representatives: P. integrifolia or P. inflata).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular phylogenies based on plastid-derived markers (Ando et al , 2005a; Kulcheski et al , 2006; Lorenz-Lemke et al , 2010) have proposed that the separation among Petunia species was related to the altitude of their occurrence, independent of corolla morphology. Nuclear and plastid genes have different coalescence times and, generally, organelle markers are geographically structured and more easily shared by different species (Chan and Levin, 2005; Mir et al , 2009), as observed in some Petunia species (Segatto et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Petunia Juss. has undergone rapid diversification during the Pleistocene climatic changes (Lorenz-Lemke et al , 2010), and molecular phylogenies did not resolve all morphological species (Kulcheski et al. , 2006; Chen et al.…”
Section: Introductionmentioning
confidence: 99%